Technical solutions to foster the global energy transition: Special issue on clean fuel conversion technologies for carbon dioxide and pollutant reduction. (February 2022) - Schiemann, M.; Böhm, B.; Chirone, R.; Senneca, O.; Ströhle, J.; Umeki, K.; Vujanovic, M.
Abstract: In the field of energy supply, the focus is shifting from conventional combustion to a variety of new energy conversion technologies. Nineteen articles in this Special Issue describe different aspects, that make combustion and combustion products attractive in the context of future sustainable energy systems. Carbon capture and recycling can bridge the current energy system and the transition to 100% renewables. The energy storage required for this is possible with combustion systems and specific synthetic fuels. In this context, bio-based fuel applications also benefit from current research and support flexible and efficient reduction of carbon dioxide emissions. All these aspects call for better experimental and numerical methods for process characterization and design. Highlights: CO2 -free combustion or even one with negative CO2 balance is within reach. Bridging technology solutions are emerging through energy storage in combustion systems. Biomass and its products are the fast track to projectable, sustainable combustion. Technical and computational advances bring solutions closer.